The importance of afuture teacher mathematical training in the system of higher pedagogical education - Fomenko, L. (Problems of Engineer-Pedagogical Education, 2018)
The author considers the questions of a future teacher mathematical training as an important constituent part of the professional training under the conditions of the reforming of the system of higher education. On the basis of the analysis of native educators’ works, specialized literature, personal pedagogical experience the author defines the place and the role of the mathematical training in the process of professional training of pedagogical specialties students. It is underlined that mathematics has a great influence on general cultural and intellectual development of a future teacher personality, formation of their scientific outlook, development of independence and creative initiative, research abilities. It is proved that mathematical knowledge is widely used while studying natural scientific and general professional disciplines in the sphere of future teachers training in the system of higher education. The sufficient level of mathematical training of future teachers contribute to conscious usage of the obtained knowledge in the further professional educational activity.